Supramolecular organization of photosynthetic membrane proteins in the chlorosome-containing bacterium Chloroflexus aurantiacus - Bína, David; Gardian, Zdenko; Vácha, František; Litvín, Radek (Photosynthesis research, 2014)
The arrangement of core antenna complexes (B808-866-RC) in the cytoplasmic membrane of filamentous phototrophic bacterium Chloroflexus aurantiacus was studied by electron microscopy in cultures from different light conditions. A typical nearest-neighbor center-to-center distance of ~18 nm was found, implying less protein crowding compared to membranes of purple bacteria. A mean RC:chlorosome ratio of 11 was estimated for the occupancy of the membrane directly underneath each chlorosome, based on analysis of chlorosome dimensions and core complex distribution. Also presented are results of single-particle analysis of core complexes embedded in the native membrane.
Keywords: buněčná membrána; Rhodopseudomonas; Microscopy, Electron; Photosynthetic Reaction Center Complex Proteins; světlo; fotosyntetická reakční centra (proteinové komplexy); Chloroflexus; Organelles; Cell Membrane; Photosynthesis; Light; organely; fotosyntéza; elektronová mikroskopie